Analysis of the protection system 10 MVA Macaas Substation in Bohol - Cubelo, Christopher P.
This Technical Report is about the distribution protection analysis of a 10MVA Substation and one (1) of its feeders of SOHECO I in Bohol. This covers the power system modeling, short circuit analysis and protection coordination of its existing distribution system. The equipment in the distribution system is modeled using the theory of symmetrical components and per-unit analysis. Carson's equations were used to model the distribution line that is based on NEA 13.2Y/7.62-kV design and construction standards. For short circuit analysis, the per-unit method is used to evaluate the three-phase (3PH), line-to-line (ll), double line-to-ground (DLG) and single line-to-ground (SLG) fault currents. The maximum and minimum fault currents available at the protection device connection points are essential in the protection coordination study and in selecting fuse rating for laterals and sublateral. Fuse-to-fuse coordination is simplified through the use of manufacturer's fuse coordination table. A time delay margin of O.3second and O.5second and used at maximum fault current for Phase and Ground Time Over-current (TOC) respectively for relay-to-relay coordination utilizing the "What-if-Analysis and Goal Seek" function of MS Excel.